A CASE REPORT ON RARE PRESENTATION OF MULTIPLE UTERINE TORSIONS IN A WISTAR ALBINO RAT - P. Jalantha; R. Rajendran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Uterine torsion is twisting of uterus or its horn perpendicular to its long axis. This is a case report of uterine torsion in an adult Wistar Albino breeder. The rat was in advanced stage of gestation with no overt signs of illness. The rat was found dead with distended abdomen and four dead pups beside her in her cage. On post mortem examination, 270o uterine torsion was observed in left uterine horn in between the two dead foetuses present and there was a 360º torsion between the caudal foetus and the cervix. One dead fetus was observed in right uterine horn. Uterine torsion in this case was attributed to the foetus-maternal disproportion. Occlusion of uterine blood vessels leads to extensive uterine damage and consequent sequestration of blood to uterus might have resulted in hypovolemic shock and death of the rat. Being a rare condition in rats, uterine torsion should always be considered as a complication in parturition.